2021
DOI: 10.1097/01.hjh.0000746304.97750.89
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association Between Depression and Incident Hypertension-an Updated Systematic Review and Meta-Analysis

Abstract: Objective: Background: The association between depression and cardiovascular disease (CVD) is well documented. However, depression has also been proposed to be involved in the pathological pathways linking the main risk factors of CVDs. Several studies including one meta-analysis have suggested that depression may be an independent risk factor for hypertension. Objective:To evaluate the relationship between depression and incident hypertension Design and method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies showed that anxiety and depression may be related to the rise of BP while other studies showed a transient sympathetic mediated rise in BP due to stress (72)(73)(74)(75). Though more studies are required to undoubtedly establish a direct relationship between stress, anxiety, and depression with hypertension, stress-whether emotional, social, cultural, or occupational-may lead to several illnesses including the development of hypertension (76).…”
Section: Experiencing Stress Throughout the Life Coursementioning
confidence: 99%
“…Some studies showed that anxiety and depression may be related to the rise of BP while other studies showed a transient sympathetic mediated rise in BP due to stress (72)(73)(74)(75). Though more studies are required to undoubtedly establish a direct relationship between stress, anxiety, and depression with hypertension, stress-whether emotional, social, cultural, or occupational-may lead to several illnesses including the development of hypertension (76).…”
Section: Experiencing Stress Throughout the Life Coursementioning
confidence: 99%